PENGARUH PENDIDIKAN KEWIRAUSAHAAN, SELF EFFICACY DAN LOCUS OF CONTROL PADA NIAT BERWIRAUSAHA - Lanang Agung Adnyana, I Gusti; Purnami, Ni Made (E-Jurnal Manajemen, 2016)
Unemployment and poverty remain a major problems faced by Indonesia today and in the next few years. Ironically, the highest unemployment rate was actually created by a well-educated group. One of the alternative to solve the unemployment problem is to empower the society and well-educated group through entrepreneurship programs. The purpose of this research is to analyze the influence of entrepreneurship education, self-efficacy and locus of control on entrepreneurship intentions of the undergraduate students. The location of this research at Economics and Business faculty of Udayana University. The samples used were 100 people. Research using purposive sampling techniques and data was collected by questionnaire. The analysis technique used in this research is multiple linear regression. Based on the results of the analysis, it found that entrepreneurship education, self-efficacy and locus of control, have positive and significant impact on student entrepreneurship intentions. Normal 0 false false false EN-US X-NONE X-NONE Unemployment and poverty remain a major problems faced by Indonesia today and in the next few years. Ironically, the highest unemployment rate was actually created by a well-educated group. One of the alternative to solve the unemployment problem is to empower the society and well-educated group through entrepreneurship programs. The purpose of this research is to analyze the influence of entrepreneurship education, self-efficacy and locus of control on entrepreneurship intentions of the undergraduate students. The location of this research at Economics and Business faculty of Udayana University. The samples used were 100 people. Research using purposive sampling techniques and data was collected by questionnaire. The analysis technique used in this research is multiple linear regression. Based on the results of the analysis, it found that entrepreneurship education, self-efficacy and locus of control, have positive and significant impact on student entrepreneurship intentions.
Keywords: Entrepreneurship education, self efficacy, locus of control, entrepreneurial intentions